Polymeric Materials from Renewable Resources - Abdulkarim Ali Al Motawwah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The growing worldwide interest in renewable polymers may be attributed to both worries about the environment and the limited availability of petroleum. There are three types of polymers that fall under the category of renewable: natural polymers, synthetic polymers made from bioderived monomers, and microbial fermentation polymers. While certain natural polymers are used extensively in the production of consumer goods, others are mostly ignored. The processes of isolating, purifying, chemically modifying, and physically modifying natural polymers all need to be improved. A synthetic polymer made from bio-based lactic acid is called poly(lactic acid). It can be worked with in the same manner as other thermoplastics, but the exorbitant cost of the material prohibits its widespread use. Increased interest in researching and developing biodegradable polymeric materials may be attributed to the recent appearance of the first commercially available biodegradable polymeric materials on store shelves. Even in potentially fruitful applications like as packaging and mulch films, the majority of currently used polymers are not being replaced because of either poor performance or expensive costs. Rarely are either petroleum or renewable polymers used in isolation. The processes of blending and compositing increase productivity. Composites made from renewable materials came before polymers. The mechanical characteristics of polymers may be improved by fibers. Because of the availability of renewable raw ingredients, cellulose fiber-reinforced polymers are making a comeback. The majority of plant parts are made of cellulose. The majority of naturally occurring polymers are functional when combined with hydrophilic cellulose. Filler reinforcement is very necessary for renewable polymers to have in order for them to have reduced softening temperatures and moduli. One of the benefits is that the hydrophilic compatibility of the mineral filler with the majority of natural polymers. Natural polymers that are hydrophilic and water-soluble The fact that it is soluble in water hastens the process of disintegration, but its sensitivity to moisture restricts its use. Blends of natural and renewable polymers as well as multilayer constructions may result in improved characteristics. Blends have the potential to provide low-cost goods with superior performance. The value of renewable polymers is being increased via the use of inventive blends and composites.